Theoretical investigation of the swelling of polysaccharide microgels in sugar solutions. Issue 5 (15th May 2018) - van der Sman, R. G. M.
Abstract : In this paper, we explain the increased swelling of crosslinked polysaccharide microgels by the increase of sugar concentration using a modified Flory–Rehner theory. Abstract : In this paper, we explain the increased swelling of crosslinked polysaccharide microgels by the increase of sugar concentration using a modified Flory–Rehner theory. This theory is validated via the investigation of the swelling of dextran microgels in sugar solutions, which can be viewed as a model system for crosslinked starch in sugar solution and custard. An essential part of our modified theory is that starch perceives the sugar solution as an effective solvent rendering a certain hydrogen bond density. Our simulations show that the often experimentally observed maximum in swelling of starch at 20% sugar concentration is probably due to the fact that equilibrium is not reached within practical time scales. Also, we discuss the use of our theory as a tool in sugar reformulation issues of custard. From simulation results one can produce a state diagram showing which formulations render a creamy, space-filling network.